Quantitative Two-Dimensional Ultrastructural Distribution of Rh(o)(D) Antigenic Sites on Human Erythrocyte Membranes(*) - Nicolson, Garth L. (Proc Natl Acad Sci U S A, 1971)
A method is described for determining the two-dimensional distribution of specific antigens on cell surfaces, and is applied to the D antigen of the Rh antigenic system. Rh-positive human erythrocytes are allowed to react with purified (125)I-labeled human anti-Rh(o)(D) γ-globulin antibodies, and the sensitized cells are then lysed at an air-water interface. The residual cell membranes are spread flat by surface forces, and are picked up on a carbon-strengthened collodion-coated electron microscope grid. The membranes are then stained with ferritin-conjugated goat antibodies directed against human γ-globulins. Only Rh-positive cells sensitized with anti-Rh(o)(D) antibodies bind the ferritin-conjugated antihuman γ-globulins. The ferritin particles are found in small clusters on the membrane surface, and the number of such clusters per unit area agrees with the number of (125)I-labeled anti-Rh(o)(D) antibodies bound per unit area. The Rh(o)(D) antigenic sites appear to be molecularly dispersed on the membrane surface, but in a random two dimensional array. IMAGES: